(untitled) (Journal of EAHIL, 2025)
Selecting the most appropriate anatomical application for a university library collection presents a complex challenge, particularly when balancing pedagogical needs, technical functionality, licensing constraints, and budgetary limitations. This article presents a structured six-step methodology developed and applied at our library to support decision-making in the acquisition of an anatomical application. The process includes market exploration, functional evaluation, financial viability assessment, user trials, contract negotiation, and communication strategies. By involving both academic staff and students, and by integrating financial considerations early in the process, the methodology ensures that the selected resource aligns with curricular needs and budget constraints. The approach is designed to be adaptable and reusable, offering a practical framework for other academic libraries facing similar decisions.